PENGARUH DISIPLIN KERJA, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN BROWNIES AMANDA CABANG BALIKPAPAN - Dwi Ayuningtyas Nurul Fathiya Sumantri; Rahajeng Cahyaning Putri Cipto (STIE Madani Balikpapan, 2020)
This research aims to figure out the influence of the working discipline, motivation and leadership style to the employee’s performance of Brownies Amanda Balikpapan Branch. The type of the research is descriptive quantitative and the primary data source is taken from 71respondents. Based on the results of multiple linear regression test, the working discipline,motivation and leadership style simultaneously influence the employee’s performance of272,249. Partially, motivation variable and leadership style variable have a significantinfluence on the employee’s performance which are 4,206 and 6,794. While working disciplinevariable has no significant influence on the employee’s performance which is 1,289.